Synthesis of high purity nickel oxide by a modified sol-gel method. Issue 9 (15th June 2019) - Mateos, D.; Valdez, B.; Castillo, J.R.; Nedev, N.; Curiel, M.; Perez, O.; Arias, A.; Tiznado, H.
Abstract: Nickel oxide (NiO) powder was synthesized by a modified sol-gel method using nickel acetate, citric acid and ethylene glycol as precursors. The synthesized material was thermally annealed at 250 °C for 2 h (pre-calcination step) and at 800 °C for 1 h (calcination). Scanning electron microscopy shows formation of particles with sizes of up to 50 μm after pre-calcination and of ≲ 10 μm after calcination. Nickel, oxygen and carbon were detected by energy dispersive X-ray spectroscopy (EDS) in the pre-calcined material, while only Ni and O were found after the calcination process. X-ray photoelectron spectroscopy (XPS) indicates that the composition of the synthesized nickel oxide is close to stoichiometric. Raman and Fourier transform infrared spectra show only characteristic peaks of nickel oxide. The calcined particles have cubic crystalline structure of NiO as proved by X-ray diffraction (XRD). EDS, XPS, XRD, Raman and FTIR confirmed that high purity nickel oxide was obtained by the proposed low-cost and highly effective method. Highlights: NiO was synthesized by a green, facile, versatile and low-cost method. High purity was proved by EDS after calcination, only Ni and O were detected. XPS indicates that the NiO composition is close to stoichiometric.